The First OCCCO Pentadentate Chelates: Osmium Mediated Stepwise Oxidations of Terminal Alkynes by Pyridine N‐Oxide. Issue 11 (1st August 2020) - Lin, Jianfeng; Xu, Qiannan; Lin, Xinlei; Hua, Yuhui; Chen, Dafa; Ruan, Yonghong; Zhang, Hong; Xia, Haiping
Summary of main observation and conclusion: Oxygen atom transfer reactions between alkynes and heteroarene N ‐oxides are currently mediated by transition metal, such as gold, ruthenium or rhodium, but they have never been catalyzed by osmium. Herein, we report stepwise oxidations of terminal alkynes mediated by an osmium carbolong complex, using pyridine N ‐oxide as the oxidant, yielding novel aldehyde‐ or carboxylic acid‐coordinated osmapentalyne derivatives selectively. The mechanism was illustrated by density functional theory calculations, providing a new route for oxygen atom transfer between heteroarene N ‐oxides and alkynes. Abstract : A stepwise oxidation of terminal alkynes mediated by an osmium carbolong complex was reported. Using pyridine N ‐oxide as the oxidant, aldehyde‐ or carboxylic acid‐coordinated osmium complexes were achieved selectively. The mechanism was illustrated by density functional theory calculations, providing a new route for oxygen atom transfer reaction between heteroarene N ‐oxides and alkynes.